(untitled) (Materiali di Estetica. Terza serie, 2020)
What the East is and what Europe is are not acquired concepts of which one can give certain and unequivocal definitions. This applies both to the past and to the present. It applies both to culture in general and to philosophy in particular. As far as philosophy is concerned, it must be made clear once and for all that in both India and China there have been ways and types of thought which, although different from European ones, are equivalent to these.